Hungry ghost - Ying, Victoria (First Second, an imprint of Roaring Brook Press, 2023)
Valerie Chu is quiet, studious, and above all, thin. No one, not even her best friend Jordan, knows that she has been binging and purging for years. But when tragedy strikes, Val finds herself taking a good, hard look at her priorities, her choices, and her own body. The path to happiness may lead her away from her hometown and her mother's toxic projections, but first she will have to find the strength to seek help.